Trinidad and Tobago : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
This report provides the IMF's projections and estimates on Trinidad and Tobago's basic data; GDP by sectors of origin at constant 1985 prices and current market prices; retail price index; population, labor force, and employment in real sector; central government operations, revenue, and grants; central government expenditure and expenditure ratios in fiscal sector; summary accounts of the consolidated financial system and development banks; monetary survey, commercial bank loans, and advances in monetary sector; summary of balance of payments; direction of trade in external sectors; and so on.